Electromagnetic Analysis of Hysteresis Synchronous Motor Based on Complex Permeability Concept - S. M. Mirimani; A. Vahedi; M. R. Ghazanchaei; A. Baktash (Iranian Journal of Electrical and Electronic Engineering, 2013)
Hysteresis motor is self-starting synchronous motor that uses the hysteresis characteristics of magnetic materials to make torque. There are different methods to model this kind of motor and take into account the magnetic hysteresis characteristic of the rotor hysteresis ring. In this investigation the application of complex permeability concept is implemented to model the hysteresis loop and the hysteresis loop in inclined ellipse shape is adopted. To the best knowledge of the authors, this has not been studied before. Based on this concept, simulation of hysteresis motor in conventional configuration is done in order to obtain the output values of motor using 3D Finite Element Model (FEM). This 3D finite element model has high level accuracy and gives better insight of motor performance. Meanwhile, in order to validate the simulation results an experimental set up is provided and the output values of typical motor are measured. It is shown that there is a good agreement between experimental and simulation results.